Primary Thyroid NUT Carcinoma With High PD-L1 Expression and Novel Massive IGKV Gene Fusions: A Case Report With Treatment Implications and Literature Review - Zhou, Juan; Duan, Miao; Jiao, Qiong; Chen, Chunyan; Xing, Aiyan; Su, Peng; Tang, Juan; Zhang, Hui; Liu, Zhiyan (Frontiers in Oncology, 2022)
Background: NUT carcinoma (NC) is a rare and aggressive undifferentiated carcinoma that typically arises from midline supradiaphragmatic structures. It is uniquely driven by a NUT gene rearrangement on chromosome 15q14. Few thyroid NCs have been reported and there are no established treatment guidelines for NUT carcinoma. Method: Ultrasound-guided fine needle aspiration smear was performed for the preoperative diagnosis of thyroid lesions. Cytopathology, histology and immunochemical staining all indicated NC. Fluorescence in situ hybridization (FISH), qRT–PCR and next-generation sequencing (NGS) were used to analyse the genetic characteristics of NC. Results: We describe a rare case of thyrogenic NC in a 38-year-old male with cytological, histological, immunohistochemical and genetic features. Cytological smears and histopathological specimens showed typical features of NC. Immunohistochemistry confirmed strong immunoreactivity with NUT, EMA, P63, TTF-1 and C-myc. CK19 is positive exclusively in sudden keratosis. No immunoreactivity was found for neuroendocrine markers. FISH was applied to isolate the NUT gene on chromosome 15q14. The NGS results revealed a BRD4-NUT gene fusion, which was further confirmed by RT–qPCR. Structural variation (SV) of NUTM1 occurred in the exon region, and the mutation site was 15q14. Moreover, BRD4 single-nucleotide variation (SNV) occurs in the 3’ UTR at mutation site 19p13.12. The PD-L1 combined predictive score was over 30%. The patient received chemotherapy, followed by programmed cell death 1 (PD-1) inhibition with camrelizumab, and died 10 months after surgery. Conclusion: Thyroid NC is an extremely rare and fatal malignant tumour. It is necessary to consider NC when squamous differentiation is observed cytologically or histologically. NGS is an effective tool for obtaining the final diagnosis and obtaining a better understanding of tumour pathogenesis. A large number of IGKV gene fusions in addition to the BRD4-NUT fusion may play a role in the pathogenesis and immunotherapy response of NC. Immunotherapy for NC remains to be explored due to the rarity of this aggressive malignancy.